2006
DOI: 10.1080/138540491005875
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Neuropsychological Effects of Adjuvant Chemotherapy Treatment in Women Treated for Breast Cancer

Abstract: Given the improvement in mortality rates associated with breast cancer, the importance of understanding the long-term neuropsychological consequences of chemotherapy is becoming increasingly vital. This study applies meta-analytic techniques to the scant literature on the relationship between contemporary adjuvant chemotherapy treatment for breast cancer and cognitive dysfunction as examined through neuropsychological indices. Seven studies (involving more than 300 participants) were selected from over 200 pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 32 publications
7
133
1
4
Order By: Relevance
“…The present, cross-sectional study was conducted among patients of 13 Dutch community hospitals who received ACchemotherapy before the start of hormonal therapy. Inclusion criteria for the TEAM-trial were: (1) histologically/cytologically confirmed adenocarcinoma of the breast followed by intended curative surgery; (2) Exclusion criteria were: (1) palliative treatment, inflammatory breast cancer, positive supraclavicular nodes or ulceration/infiltration of local skin metastasis; (2) evidence of distant metastases; (3) previous adjuvant hormonal treatment; (4) uncontrolled cardiac disease; (5) psychiatric disorders preventing proper informed consent; (6) concomitant malignancies or other significant malignancies within the past 5 years; (7) or other serious illnesses; (8) HRT use not stopped at least 4 weeks prior to randomization; (9) bilateral tumor; (10) neo-adjuvant chemotherapy. For the current neuropsychological side study additional inclusion criteria were: (1) free of CNS disease; (2) no signs of dementia according to a dementia screenings tool (7 minutes screen) [14]; (3) being fluent in Dutch; and (4) use of the originally assigned hormonal agent for at least six months.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The present, cross-sectional study was conducted among patients of 13 Dutch community hospitals who received ACchemotherapy before the start of hormonal therapy. Inclusion criteria for the TEAM-trial were: (1) histologically/cytologically confirmed adenocarcinoma of the breast followed by intended curative surgery; (2) Exclusion criteria were: (1) palliative treatment, inflammatory breast cancer, positive supraclavicular nodes or ulceration/infiltration of local skin metastasis; (2) evidence of distant metastases; (3) previous adjuvant hormonal treatment; (4) uncontrolled cardiac disease; (5) psychiatric disorders preventing proper informed consent; (6) concomitant malignancies or other significant malignancies within the past 5 years; (7) or other serious illnesses; (8) HRT use not stopped at least 4 weeks prior to randomization; (9) bilateral tumor; (10) neo-adjuvant chemotherapy. For the current neuropsychological side study additional inclusion criteria were: (1) free of CNS disease; (2) no signs of dementia according to a dementia screenings tool (7 minutes screen) [14]; (3) being fluent in Dutch; and (4) use of the originally assigned hormonal agent for at least six months.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…A recent meta-analysis using seven cross-sectional studies suggests small to medium cumulative effect-sizes across eight cognitive domains, with lower cognitive functioning for breast cancer (BC) patients compared to healthy controls [1]. In recent years, several prospective longitudinal studies are published, of which most, but not all, found subtle negative influences of chemotherapy on cognitive functioning in a subset of patients [2].…”
mentioning
confidence: 99%
“…Psychomotor performance in depressed subjects may be further influenced by other factors, such as hospitalization status/duration, severity, subtype and duration of depression, and medication (Bashir et al, 2013). Many studies have addressed specifically effects of medication on psychomotor speed (Aldenkamp et al, 2002;Bashir et al, 2013;Stewart et al, 2006). First-line medication for depression often includes substances (e.g., fluoxetine, venlafaxine, and paroxetine) liable to affect cognitive and function performance (Bashir et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recently, in an attempt to overcome such limitations, several computerized versions have emerged, which are able to measure the response time more precisely, requiring less time to administer, and generating instant scoring (Wilken et al, 2003). The FTT is now part of several recent batteries, such as the Computerized Neurocognitive Battery (Coleman, Moberg, Ragland, & Gur, 1997;Gur et al, 2010), the Automated Neuropsychological Assessment Metrics-ANAM 4tm Reeves, Winter, Bleiberg, & Kane, 2007;Wilken et al, 2003), the FePsy (Aldenkamp et al, 2002;Stewart et al, 2006), and the Neurotrax TM Mindstreams TM (Dwolatzky et al, , 2004Schweiger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation